KETRAMPILAN KEWIRAUSAHAAN SEBAGAI PEMBERDAYAAN POTENSI ANAK ASUH YAYASAN PANTI ASUHAN KRISTEN JAWA TIMUR DI MALANG - Tri Ist. Wardani; Asminah Rachmi; Musthofa Hadi; Tri Ramadani A; Dwi Sudjanarti; Umi Khabibah (Jurnal Pengabdian kepada Masyarakat, 2020)
The purpose of this PkM activity is to empower the potential of foster children (girl) of the East Java Christian Orphanage Foundation as the target audi ences to spark motivation and creativity so that they become independent individuals. Empowerment is carried out by providing entrepreneurship skills training. The material studied is Basic Knitting using the Single Crochet Stitch, Half Double Crochet Stitch and Double Crochet Stitch technique to create a Semi Solid Granny Square pattern which will produce a product in the form of a Tote Bag. PkM activities are divided into 3 modules, the first is theoretical briefing about the objectives, benefits and tips, as well as the importance of having an entrepreneurial spirit and high motivation to learn various kinds of skills, the second is a theoretical explanation of basic knitting techniques / Crocheting and the Semi Solid Granny Square pattern for making Tote Bags, and the third practice and practice to produce a product that is worth selling so that it can be marketed so that it can help with economic problems and welfare in their families. From the training that was held for 2 days, and assistance for independent learning online through Whatsapp media to 10 foster children (girl), 4 gilrs were successful with their commitment to produce the final product in the form of a Tote Bag, even 1 of them managed to enrich and sharpen her own skills by combining the thread color in the final product. Based on the results of the evaluation, it can be concluded that the training ran smoothly and effectively and brought benefits, because the target audiences could absorb the knowledge conveyed and was able to produce the finished product as targeted from the start.